The Efficiency of Bio-adsorption of Heavy Metals from Pharmaceutical Effluent by Rumex crispus L. Seed - Parisa Ziarati; Mahyar Zahirnejad; Jinous Asgar Pahanh (Islamic Azad University, 2017)
The programs of managing waste materials in developing countries are often unsatisfactory and the unreasonable disposal of waste is a major issue in the worldwide. The main aim of the current study is to: Assess the applicability of Rumex crispus L. in removing heavy metals from the contaminated wastewater effluent form Pharmaceutical laboratories by bio-adsorption method. The dried R. crispus L. seeds were purchased from recognized herbal plant markets randomly in Tehran in May 2016 in order to investigate the influence of R. crispus seeds as an amendment to remove or decrease chemical forms of Co, Pb, Cu, Zn and Ni. Experimental parameter were as follows: pH, temperature, dose of bio-adsorbent R. crispus L. seeds, contact time, particle size mesh were studied. Results revealed that bio-adsorption capacity of Lead, Zinc, Copper, Cobalt and Nickel increases with increasing initial adsorbent concentration and reaches at maximum after a 2% initial concentration of S. incisa seeds concentration value. Heavy metals adsorption ranged from 83.5 -91 % after agitation for 1 week (equilibration time), and there was no significant further increase in % sorption of them after the equilibration time (P ≥ 0.05). This research area of using models for resolving nature of heavy metals complexation and sequestrations mechanism at heavy metals-bio-adsorption interface have been less explored . The results represents a critically important mechanism in the scientific ability which should be investigated in future research to unravel complex surface heavy metal sorption mechanism on the bio-sorbent's surface by using various chemical modeling approaches. Current research is suggested for the characterization of novel bio-adsorbents from other waste of herbal plants, agriculture/food-industry with maximum heavy metals sorption capacities to promote large-scale use of bio-adsorbents.